Feminists Birthing a New Way of Being Church - Abraham, Kochurani (Liberatio)

(untitled) (PUM, 2024)
This text delves into the intersection of feminist theology and ecclesiological transformation, using Sisters in Solidarity (SIS) as a case study. It explores how feminist perspectives challenge gendered hierarchies within religious institutions, focusing on birthing change and fostering feminist solidarity. The narrative unfolds with a critical analysis of the Church’s historical and contemporary treatment of women, especially in light of clergy sexual abuse scandals. It discusses the emergence of SIS as a proactive force, advocating for justice, healing and empowerment for marginalised individuals within the Church. The text also delves into theological underpinnings, emphasising the embodiment of the divine in female experiences and the importance of solidarity as a catalyst for transformative actions. Ultimately, it calls for a reimagining of ecclesiastical structures towards inclusivity, equality and a deeper engagement with feminist principles for a more just and compassionate Church.